Visionary Leadership in Building Achievement Characters in Elementary Schools - Muh. Hambali (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study is to describe the visionary leadership model in shaping the character of student achievement in SD Unggulan Al-Ya'lu Malang. This research uses descriptive qualitative. Retrieval of data using observation, interviews and documentation. Observations are used to support the leadership process announced by the vision in the form of actions, documentation used to measure vision planning for students and interviews that are used to explore the development policy of school principals, deputy principals and teachers to students at school. This data analysis uses data reduction, data presentation and conclusion. Based on this study the results of school development research involving people who see the school through the example of the principal and learning teachers use contextual learning. Means of learning support the ecosystem that is built, namely the synergy of the three learning environments, family, school and community.